Characteristics of fuel oil obtained from oil of the Krapivinskoe oilfield (report 2) - Tatiana V. Cheshkova; Татyana А. Sagachenko; Elena Yu. Kovalenko; Alexandra S. Vishnevich; Evgeniya B. Golushkova; Raisa S. Min (Известия Томского политехнического университета: Инжиниринг георесурсов, 2025)
Relevance. The need to obtain new data on the pattern of thermal transformations of resin, asphaltene and oil components of the fuel oil subjected to thermal or thermocatalytical treatment. These data will help to improve the efficiency of thermal and thermocatalytic treatment of fuel oil for increasing the yield of desired products. Aim. To study the structural organization of resin-asphaltene substances and the molecular composition of oil components isolated from the residue of crude oil produced at the Krapivinskoe field and the products of its thermal destruction. Methods. Transmission electron microscopy, X-ray phase analysis, IR spectroscopy, 1H NMR spectroscopy, structural group analysis and gas chromatography-mass spectrometry. Results. The authors have carried out the comparative study of the composition and structure of resin and asphaltene macromolecules and the molecular composition of residue obtained in the course of atmospheric distillation of Krapivinskoe oil and liquid products of its thermal and initiated cracking. It was found out that asphaltenes of the initial fuel oil and its cracking products have a predominantly amorphous structure. The presence of stacking ordered crystallites is less characteristic of asphaltenes isolated from liquid products of initiated cracking, which is due to the presence of a developed alkyl chain configuration in their macromolecules. In cracking processes, the mean asphaltene molecule becomes smaller due to a lower number of aromatic and naphthenic rings in the polycyclic system. On the contrary, the mean resin molecules become larger, mainly due to an increase in the number of aromatic cycles and paraffin carbon atoms in alkyl fragments. Paraffin carbon atoms in the structure of thermocracked asphaltenes are included into the methyl groups only, while in the structure of asphaltenes subjected to the initiated cracking they are mainly included into the long linear or weakly branched alkyl chains. In the mean molecules of the resin samples under study, paraffin carbon atoms form both short and relatively long alkyl substituents. Their fraction in the structure of mean resin molecules of cracking products is much higher than that in the structure of the mean resin molecule of the initial fuel oil. A distinctive feature of the oil components of the converted  fuel oil is a wider range of identified compounds. They also include branched alkanes, n-alkylcyclopentanes, n-alkyldimethylbenzenes, phenyl derivatives of benzene and naphthalene, fluorenes, tetra-, penta- and hexacyclic aromatic hydrocarbons, benzo- and dibenzothiophenes, naphtho- and naphthobenzothiophenes. The products of destruction of resin-asphaltene substances of the initial fuel oil and its oil components are considered as a likely source of these compounds.